Effect of grain‐scale pressure variations on garnet growth: a numerical approach. (9th August 2016) - Zhong, X.; Vrijmoed, J.C.; Tajčmanová, L.
Abstract: Grain‐scale pressure variations have recently been investigated due to its significant effect on the observed microstructures and chemical redistribution in metamorphic rocks. In this study, the impact of grain‐scale pressure variation on a growing garnet grain is investigated. We model prograde garnet growth at fluid‐saturated conditions and sufficiently low temperature (<650 °C) to avoid modification of the inner part of the grain by diffusion. The method uses the Perple_X computer program package combined with Matlab ® scripts allowing for a heterogeneous fluid pressure distribution around the growing grain. It is shown that the pressure variation around the grain may result in an asymmetric chemical zonation. Motivated by the result, we apply the model to selected published prograde paths to evaluate the magnitude of the pressure variation that is necessary for the development of the asymmetric zoning preserved in the samples. The magnitude of such a pressure gradient in the selected samples may correspond up to 1 kbar. Finally, it is demonstrated that the modelling of asymmetric chemical zoning in garnet under a pressure gradient may improve the precision of thermobarometric constraints. The numerical model evaluates the effect of the pressure gradient on a growing grain and thus can serve as a benchmark tool in future development of fully coupled models involving rock deformation and mineral reactions.